Eccentric Activation Patterns in the Left Ventricular Outflow Tract during Idiopathic Ventricular Arrhythmias Originating From the Left Ventricular Summit: A Pitfall for Predicting the Sites of Ventricular Arrhythmia Origins. (August 2019) - Yamada, Takumi; Kumar, Vineet; Yoshida, Naoki; Doppalapudi, Harish
Abstract : Background: Idiopathic ventricular arrhythmias (VAs) originating from the left ventricular summit (LVS) can be ablated from the great cardiac vein and remote endocardial sites. The ablation sites are determined by mapping in the great cardiac vein and left ventricular outflow tract. This study investigated whether that mapping could accurately predict the sites of LVS-VA origins. Methods: We studied 26 consecutive patients with idiopathic LVS-VA origins that were identified in the basal and apical LVS in 15 and 11 patients, respectively. Results: Radiofrequency catheter ablation of the apical LVS-VAs was successful in the great cardiac vein in 9 patients and in the apical LV outflow tract in 2. That of the basal LVS-VAs was successful in the aortomitral continuity in 9 patients, at the junction of the left and right coronary cusps in 4, and in the left coronary cusp in 2. Three apical LVS-VAs exhibited an eccentric endocardial activation pattern that was from the basal to apical LV outflow tract. In 11 basal LVS-VAs, the activation pattern was eccentric because the ventricular activation within the great cardiac vein in the apical LVS was earlier than that in the basal LV outflow tract. In 2 basal LVS-VAs, the activation pattern was eccentric because a relatively early ventricular activation was recorded at multiple sites away from the successful ablation site. Conclusions: Eccentric activation patterns often occurred during idiopathic LVS-VAs, which could mislead the catheter ablation of those VAs. Understanding such eccentric activation patterns was suggested to be able to improve the outcomes of the catheter ablation of those VAs by the anatomic approach.